Ultrasensitive sensing with three-dimensional terahertz metamaterial absorber. (10th April 2018) - Tan, Siyu; Yan, Fengping; Wang, Wei; Zhou, Hong; Hou, Yafei
Abstract: Planar metasurfaces and metamaterial absorbers have shown great promise for label-free sensing applications at microwaves, optical and terahertz frequencies. The realization of high-quality-factor resonance in these structures is of significant interest to enhance the sensing sensitivities to detect minute frequency shifts. We propose and demonstrate in this manuscript an ultrasensitive terahertz metamaterial absorber sensor based on a three-dimensional split ring resonator absorber with a high quality factor of 60.09. The sensing performance of the proposed absorber sensor was systematically investigated through detailed numerical calculations and a maximum refractive index sensitivity of 34.40% RIU −1 was obtained. Furthermore, the absorber sensor can maintain a high sensitivity for a wide range of incidence angles up to 60° under TM polarization incidence. These findings would improve the design flexibility of the absorber sensors and further open up new avenues to achieve ultrasensitive sensing in the terahertz regime.